Exercise therapy in medical rehabilitation: Study protocol of a national survey at facility and practitioner level with a mixed method design - Geidl, Wolfgang (Contemp Clin Trials Commun, 2018)
BACKGROUND: The importance of physical activity and the orientation of exercise therapy in rehabilitation has changed for many chronic health conditions. Exercise therapy is the most applied therapy form within multidisciplinary rehabilitation programs for almost all chronic health conditions. Despite the scientifically discussed need to refine exercise therapy, there is relatively little knowledge of how exercise therapy is actually conducted. This study protocol describes the methodological procedure used in the project “Exercise therapy in medical rehabilitation: a survey at facility and practitioner level”, which aims to take a national survey of exercise therapy in rehabilitation practice in Germany. METHODS: The project was implemented using an explanatory sequential mixed method design. Quantitative and qualitative methods were integrated in two consecutive project phases. Phase 1 used a standardized, quantitative written survey of the heads of exercise therapy departments to compile a national overview of concepts and process features of exercise therapy of individual rehabilitation facilities. Phase 2 recorded individual perspectives and opinions concerning exercise therapy goals, content and methods and current developments in the rehabilitation context (e.g., physical activity promotion, interdisciplinarity, standardization) of exercise therapy practitioners. Over the course of two one-and-a-half day workshops, central themes were introduced and prepared with standardized written individual surveys from Phase 1 and combined with qualitative surveys using facilitated group discussions (focus groups in mixed methods design). DISCUSSION: The project generates a comprehensive picture of exercise therapy in medical rehabilitation at facility level and inserts further information at the practitioner level into this context. The chosen methodology of a mixed method design combines the perspective of the facility with that of the practitioner, thus allowing for a complex and multifaceted description of the status quo in exercise therapy practice and makes it possible to identify facilitators and barriers for the refinement of exercise therapy in specific everyday rehabilitation. These findings form the basis for the systematic development of quality exercise therapy in rehabilitation, in particular in terms of the refinement, implementation and dissemination of biopsychosocial concepts of exercise therapy.